Salami asked the following: Question: 6 (2x  3) = 42 Multiplying out brackets ...  6 × 2x = 12x
= 12x + 18
Have I gone completely wrong? I don't really understand. :( Thanks for this, Salami! You have done very well, but the answer is a big YES! Hopefully some others will have spotted it too. Here's where you went wrong: = 12x  18
You treated 12x  18 as 12x  18x. Let's try again: 12x  18 = 42 (it really IS useful to work on the whole expression, not just bits of it!) Now you must simplify the expression by adding 18 to both sides: 12x  18 + 18 = 42 + 18 This becomes: 12x = 60 which simplifies to: x = 5 You can now check this is correct: 6 (2x  3) = 42 ... 6 (2×5  3) = 42 ... 6 (7) = 42 ... which is correct. So 42 really is the answer to life, the universe and everything!
